Radionuclides in oncology clinical practice – review of the literature. Issue 42 (4th October 2017) - Luna Pais, Helena; Alho, Irina; Vendrell, Inês; Mansinho, André; Costa, Luís
Abstract : Radionuclide therapy is a promising type of targeted therapy for cancer and its use is becoming more common in several types of malignant tumors. Abstract : Radionuclide therapy is a type of targeted therapy that can be useful in the treatment of several malignant tumors. Compared with other forms of systemic therapy used in cancer – including chemotherapy – it has the advantage of sparing biological structures adjacent to the tumor cells. This treatment modality has registered significant advances since its first use for the treatment of tuberculous skin lesions in the 1900s. This paper reviews the characteristics and clinical applications of therapeutic radionuclides commonly used in the oncology clinical practice, and discusses future potential applications.